Effects of soft-start exposure on the curing characteristics and flexural strength in ceramic projection stereolithography process. Issue 13 (October 2019) - Wu, Xiangquan; Lian, Qin; Li, Dichen; He, Xiaoning; Liu, Xiaodong; Meng, Jiali; Jin, Zhongmin
Abstract: Ceramic mask projection stereolithography (CMSL) is an additive manufacturing (AM) technology which is capable of implementing delicate structural designs of ceramic parts. Studies have shown that soft-start exposure mode has an effect on the polymer properties of the cured resin, such as conversion degree, curing speed etc. However, the effect of soft-start exposure on CMSL process has not received much attention. In this investigation, soft-start exposure was compared with constant exposure. The results showed that the soft-start exposure reduced the critical exposure energy (maximum reduction of 48.2%) of the slurry. The feature dimensional error of soft-start exposure was smaller than constant exposure by 25–45%. The soft-start exposure also had an effect on the strength of sintered parts. The bending samples fabricated by soft-start exposure had higher Weibull moduli (maximum increase of 47.2%), indicating that soft-start exposure stabled the curing process.